Parsimony analysis of phylogenomic datasets (I): scripts and guidelines for using TNT (Tree Analysis using New Technology). (14th July 2021) - Torres, Ambrosio; Goloboff, Pablo A.; Catalano, Santiago A.
Abstract: We discuss here the use of TNT (Tree Analysis using New Technology) for phylogenomic analysis. For such data, parsimony is a useful alternative to model‐based analyses, which frequently utilize models that make unrealistic assumptions (e.g. low heterotachy), struggle with high levels of missing data, etc. Parsimony and model‐based methods often yield trees with few topological differences, which can then be analyzed further in order to investigate whether these few topological differences are due to undesirable analysis artefacts. This is facilitated by the greater speed and computational efficiency of parsimony, which allow for a more in‐depth analysis of datasets. We here briefly describe the computationally most efficient and versatile parsimony software, TNT, which can be used for phylogenetic and phylogenomic analyses. In particular, we describe and provide a series of scripts that are specifically designed for the analysis of phylogenomic datasets. This includes scripts for concatenation of gene data files in different formats, generation of plots and datasets with different levels of gene/taxon occupancy, calculation of different support measures and phylogenetic reconstruction based on concatenated matrices and single genes. The execution of the scripts is also demonstrated with video clips (https://www.youtube.com/channel/UCpIgK8sVH‐yK0Bo3fK62IxA ). Lastly, we describe the main commands and functions that enable efficient phylogenomic analyses in TNT.